Crowdfunding, demand uncertainty, and moral hazard: A mechanism design approach - Roland Strausz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
Crowdfunding challenges the traditional separation between finance and marketing. It creates economic value by reducing demand uncertainty, which enables a better screening of positive NPV projects. Entrepreneurial moral hazard threatens this effect. Using mechanism design, mechanisms are characterized that induce efficient screening, while preventing moral hazard. "All-or-nothing" reward-crowdfunding platforms reflect salient features of these mechanisms. Efficiency is sustainable only if expected gross returns exceed twice expected investment costs. Constrained efficient mechanisms exhibit underinvestment. With limited consumer reach, crowdfunders become actual investors. Crowdfunding complements rather than substitutes traditional entrepreneurial financing, because each financing mode displays a different strength.
Keywords: D82; G32; L11; M31; 330; crowdfunding; finance; marketing; demand uncertainty; moral hazard